2020
DOI: 10.3389/fnhum.2020.00309
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation During Visually Guided Finger Movements

Abstract: Computer interaction via visually guided hand movements often employs either abstract cursor-based feedback or virtual hand (VH) representations of varying degrees of realism. The effect of changing this visual feedback in virtual reality settings is currently unknown. In this study, 19 healthy right-handed adults performed index finger movements ("action") and observed movements ("observation") with four different types of visual feedback: a simple circular cursor (CU), a point light (PL) pattern indicating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…In the study of Perani et al, different degree of realism in real and VR hands, including high (realistic) and low (coarse) VR hands, led to different activation patterns [ 11 ]. However, in the study of Brand et al, they found that there was no significant difference in brain activation between virtual (more realistic) hand and shadow (less realistic) hand while observing [ 30 ], which was in line with our findings. Thus, between the VR and real context, the much closer physical characteristics of visual stimuli perceived, the much similar effects of brain activations evoked.…”
Section: Discussionsupporting
confidence: 92%
“…In the study of Perani et al, different degree of realism in real and VR hands, including high (realistic) and low (coarse) VR hands, led to different activation patterns [ 11 ]. However, in the study of Brand et al, they found that there was no significant difference in brain activation between virtual (more realistic) hand and shadow (less realistic) hand while observing [ 30 ], which was in line with our findings. Thus, between the VR and real context, the much closer physical characteristics of visual stimuli perceived, the much similar effects of brain activations evoked.…”
Section: Discussionsupporting
confidence: 92%
“…The immersive experience the VR offered to the patient demonstrates improvements to the performance of tasks and functional abilities of the patient due to brain plasticity [15,24,52]. The above finding can be explained based on brain imaging approaches and how the perceived visual feedback activates the mirror neurons reaching an improvement on prosthetics control ability [5,18,62]. Therefore, the ability to correctly perform a grabbing task with the missing limb through the embodied virtual arm ensured it is perceived by the patient as a real part of the body.…”
Section: Attitudes and Effective Responses Of The Vr Myoelectric-powered Prosthetic Trainingmentioning
confidence: 88%
“…Visual feedback (e.g., naturally reaching out and grabbing a virtual object with an amputated limb) activates the neuron networks in the brain that are involved in sensorimotor learning, called mirror neurons [54,55]. Mirror neurons can be activated through the reproduction or observation of movements [5,18,53].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in humans, TP8 region contributes to the global processing of visual information [165]. The connection between this two regions, TP8 and C3, is involved in visual and tactile perceptions, and finger movements [166, 167].…”
Section: Discussionmentioning
confidence: 99%